Implementasi Prinsip Transparansi Dalam Kaidah Islam - Sari , Dwi Novita; Previdayana, Kavita Sapna; Djasuli, Mohamad (Jurnal Ekonomika Dan Bisnis (JEBS), 2022)
Proper corporate governance is a common principle throughout the world which is to maintain organizational integrity. The problem of developing good corporate governance has grown with the financial problems of several large corporations, including Enron and WorldCom. Indonesia, the majority of which are Muslim citizens, need to understand the principles of Islamic good corporate governance in conducting business. The development of sharia entities requires operational employees to implement GCG in accordance with sharia principles. The purpose of this study is to find out how the application of the principle of openness in relation to the verses of the Qur'an is in accordance with Islamic principles. This research is a literature study using descriptive analysis.